SLANGS IN ARCTIC MONKEYS’ SONG: A STUDY OF SOCIOLINGUISTICS - Nurindra, Muhammad Faiq Athallah; Sari, Retno Purwani (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This objective of this research is to investigate social and cultural meanings while examining the English teens’ slang used by Arctic Monkeys in their songs. Achieving this research goal, a descriptive qualitative approach provided empirical stages. In the data collection stage, listening the songs and reading the lyrics of Arctic Monkeys song were the main activities. These activities were proceeded by analysing and describing the cultural and social concepts conveyed in the slang, utilizing sociolinguistic perspectives during the analysis stage. The results reveal that the slangs in Arctic Monkeys’ songs reflect the band’s social and cultural meanings, giving the lyrics a unique character. The influence of Yorkshire values involves in the creation of the slangs, adding depth and authenticity to the narratives, shaping the band’s identity, and contributing to the discourse of music culture